(untitled) (Research, Society and Development, 2020)
The evapotranspiration effluent treatment system consists of an alternative method of sanitary sewage treatment in which the processes of anaerobic digestion and evapotranspiration preponderate. The objective of this work is to analyze the operation of an evapotranspiration tank (TEvap) in the district of Bicuíba, in the city of Raul Soares-MG, and to evaluate its cost-effectiveness. The study was carried out on a single-family scale between the months of June to October, during which samples were collected once a month, totaling five collection campaigns in the area. The following analyzes were carried out to evaluate soil fertility: potassium hydrogen nitrogen, phosphorus, nitrogen content, humic substances, potassium, calcium, Magnesium, aluminum, potential acidity (H + Al), remaining phosphorus (P-rem) Organic matter, Micronutrients (Fe, Zn, Mn, Cu), Boron and Sulfur. The costs of implantation, operation, maintenance, domestic sewage influence on the soil characteristics in the system as well as the main care involved were evaluated in order to obtain an analysis of the overall performance of the evapotranspiration tank on a single family scale. It was possible to conclude that TEvap is a promising system to be implemented in rural areas of Brazil, since it offers a good cost-benefit, since it allows the treatment of domestic sewage with low implantation and maintenance costs, improving quality of the residents of the region and reducing the impacts of the environment.